(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
With the advancement of the information technology, computer has become more important for the people. Computer not only stores data but also increase the channels of storing data in digital devices like pen drive, hard disk, memory card. However, problem with these digital devices is that if data has lost it is very difficult to recover; so many researchers do research on it and suggested the method of data recovery. The term data refers to the combination of numbers or words, images, audio or video files or even a software program. Data restore is the procedure of recovery of information from media that is either corrupted or damaged physically. The data recovery software extracts the data that requires serving as an evidence from personal computers and digital devices in criminal cases that involve frauds, murder, corruption, money laundering, assault, smuggling, email scams, digital abuse, matrimonial frauds and much more. Here in this study, we combine probably all data recovery software and we will conclude that the best data recovery software in forensic sound manner. This study will help in future study to understand the overview of computer forensics data recovery software.